Manajemen Kompensasi dan Kinerja Karyawan pada Industri Makanan - Wendy Souisa (Movere Journal, 2022)
This study aims to determine the effect of compensation management on employee performance in the food and beverage industry in Makassar. From this study found that there is a significant influence between compensation management on the performance of employees of the food and beverage industry in Makassar City. With the calculated F value of 19.116 and R square of 0.165. This study found that management and employees must be able to implement an effective compensation policy that can be mutually beneficial. This finding proves that there is a significant relationship between compensation management and employee performance, where employee performance depends on planning, implementing and controlling effective compensation management.